2017
DOI: 10.1136/bmjopen-2017-016128
|View full text |Cite
|
Sign up to set email alerts
|

What are the associations between neighbourhood walkability and sedentary time in New Zealand adults? The URBAN cross-sectional study

Abstract: ObjectivesWe estimated associations between objectively determined neighbourhood ‘walkability’ attributes and accelerometer-derived sedentary time (ST) by sex, city or type of day.DesignA cross-sectional study.SettingThe URBAN (Understanding the Relationship between Activity and Neighbourhoods) study was conducted in 48 neighbourhoods across four cities in New Zealand (August 2008 to October 2010).ParticipantsThe response rate was 41% (2029 recruited participants/5007 eligible households approached). In total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…The environmental attributes were assessed using a previously developed self-report instrument with known measurement properties (19,26,27). Some recent research using objectively-assessed measures of the built environment has failed to observe significant associations with accelerometerassessed sedentary time (16,18). Further comparative research is needed to determine whether differential associations are observed between perceptions and objectively-assessed built environment features with sedentary behaviors.…”
Section: Accepted Manuscript 17mentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental attributes were assessed using a previously developed self-report instrument with known measurement properties (19,26,27). Some recent research using objectively-assessed measures of the built environment has failed to observe significant associations with accelerometerassessed sedentary time (16,18). Further comparative research is needed to determine whether differential associations are observed between perceptions and objectively-assessed built environment features with sedentary behaviors.…”
Section: Accepted Manuscript 17mentioning
confidence: 99%
“…While there is some evidence suggesting potential associations between perceptions of the built environment and sitting time, a recent review concluded that the pattern of associations within the published studies was modest and inconsistent (15). In addition, some more recent studies assessing associations between objective measures of the environment and sedentary time have failed to identify significant associations (16)(17)(18). The inconsistent relationships between environmental attributes and sedentary behavior may be because such relationships A C C E P T E D M A N U S C R I P T 4 are less direct and strong than are those for physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, longitudinal study with adults from Nerima and Kanuma cities, in Japan, did not find association between screen time and access to different types of destinations [28]. In addition, studies conducted with adults from high-income countries like New Zealand, Belgian, and Netherlands that evaluated sedentary behavior by accelerometers did not find significant association with built environment variables [29,30] or found positive association, showing that people who lived in places with better walkability, for example, had more minutes of sitting time, a result that not was expected [17].…”
Section: Resultsmentioning
confidence: 94%
“…In modern cities and public living areas that we have built with our own hands, vehicles and buildings are mostly included. As a result, people's activities, such as walking, cycling, and climbing, are severely restricted (12). We spend most of our daily life in our cars on the way to work, shopping and even to gyms.…”
Section: Discussionmentioning
confidence: 99%